The Influence of Creative Organizational Culture on the Sustainable Innovation Process at PT Paragon Technology and Innovation - Galant M Ahmed; Guntur Haludin; Vicka Ellianna Ristanti; Tasya Alivia Putri; Irgi Saeful Rizky; Dhafa Herlambang Wisanggeni (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The aim of this research is to ascertain whether positive or negative internet reviews have an impact on consumer trust in a business. The methodology of this investigation is quantitative. 2019 active management students who have purchased Roughneck 1991 items on Shopee Marketplace form the population for this analysis. A total of 94 participants were surveyed for this analysis. Primary data collection was carried out by sending questionnaires, so this research relies entirely on this method. Multiple regression analysis in SPSS 25 was used to analyze the data in this research. The t-test findings of this study indicate that good online customer reviews significantly increase consumer trust, whereas online customer ratings do not. Consumer confidence in Roughneck 1991 products on Shopee Marketplace increased as a result of the positive and statistically significant feedback they received from other customer evaluations and ratings posted online. It is hoped that in the future academics will include more characteristics that theoretically also impact customer trust. Researchers can provide Roughneck 1991 marketing advice to improve the quality and quantity of their merchandise.